A comprehensive review of Zero Trust Network Architecture (ZTNA) and deployment frameworks - Mahmod Attar Bashi, Zainab Senan; Senan, Shayma (International Islamic University Malaysia, 2025)
The zero trust (ZT) approach has initiated significant advancements in network security, addressing the limitations oftraditional security models. Traditional network security approaches have faced challenges adapting to modern trends such as bring your own device (BYOD) and cloud computing, resulting in increased complexity in meeting new security requirements. The zerotrust security model operates on the principle that no entity within the network, whether internal or external, is inherently trusted. Therefore, all users and devices must undergo strict authentication and authorization processes prior to accessing organizational resources. This review paper provides a comprehensive analysis of zero trust network architecture (ZTNA) and outlines a general deployment framework model, highlighting the critical role of zero trust in modern network security.